Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have a series:

$$ \sum^\infty_{n=1}{\bigg(\frac{1}{\sqrt{n}}-\frac{1}{\sqrt{n+2}}\bigg)} $$

and I thought it is a divergent series since

$$ \sum{\big(f(x)-g(x)\big)} = \sum{f(x)} - \sum{g(x)} $$

and so the series equals to

$$ =\sum^\infty_{n=1}{\frac{1}{\sqrt{n}}}-\sum^\infty_{n=1}{\frac{1}{\sqrt{n+2}}} $$

and we know that $\sum^\infty_{n=1}{\frac{1}{\sqrt{n}}}$ is divergent, so the whole series is divergent. But it turns out that it is convergent and the answer is $1+\frac{1}{\sqrt{2}}$.

How do you prove that it is convergent and calculate the answer? The only way I know how to compute an answer for a series is via a geometric series and there seems to be no way to make it into a geometric series!

share|improve this question
2  
    
@labbhattacharjee - Oh wow thank you so much! I totally forgot telescoping series existed! –  Derek 朕會功夫 Apr 4 at 5:35
4  
Consider $\sum_{i=1}^\infty 1$, which diverges, and $\sum_{i=1}^\infty 1$, which diverges. But $\sum_{i=1}^\infty (1-1)$ obviously converges to 0. –  MJD Apr 4 at 5:43

4 Answers 4

up vote 6 down vote accepted

The rule you quoted above $\sum (f(x)-g(x)) = \sum f(x) - \sum g(x)$ is not correct if one or both of the series on the right is divergent. In this case, both $\sum \frac{1}{\sqrt{n}}$ and $\sum \frac{1}{\sqrt{n+2}}$ are divergent.

As indicated in the comments, to evaluate this series, you should telescope the series.

share|improve this answer
5  
To further elaborate as to why we cannot say $\sum f(x) - g(x)$ diverges if $\sum f(x)$ and $\sum g(x)$ are individually divergent, consider the example $$\sum_{k=1}^\infty \frac{1}{k(k+1)} < \sum_{k=1}^\infty \frac{1}{k^2} < \infty.$$ But we can of course write $$\frac{1}{k(k+1)} = \frac{1}{k} - \frac{1}{k+1},$$ and we know that $$\sum_{k=1}^\infty \frac{1}{k}$$ is divergent. Indeed, even more trivially, $$\sum_{k=1}^\infty 0 = 0,$$ yet we could write it as $$\sum_{k=1}^\infty (1-1) = \sum_{k=1}^\infty 1 - \sum_{k=1}^\infty 1 = \infty - \infty.$$ –  heropup Apr 4 at 6:08
    
The summation rule is valid if both of the individual series converge. Just check the partial sums. –  Ryan Reich Apr 4 at 15:09
    
@RyanReich Yes you're right. –  Ted Apr 4 at 15:43
    
@heropup Those are a nice set of examples; I think you should post that comment as an answer. –  Mike Miller Apr 5 at 0:30

Hint

Write $$\frac{1}{\sqrt{n}}-\frac{1}{\sqrt{n+2}}=\bigg(\frac{1}{\sqrt{n}}-\frac{1}{\sqrt{n+1}}\bigg)+\bigg(\frac{1}{\sqrt{n+1}}-\frac{1}{\sqrt{n+2}}\bigg)$$ and then telescope.

share|improve this answer

First to address your concern,

$$\sum_{n=1}^\infty \bigg(f(x)-g(x)\bigg)=\sum_{n=1}^\infty f(x)-\sum_{n=1}^\infty g(x)$$

is valid only when both $f$ and $g$ are convergent. An infinite sum is nothing more than the limit of partial sums, and the above is equivalent to writing,

$$\lim_{n\to\infty} (S_{n_1}-S_{n_2}) = \lim_{n\to\infty} S_{n_1} - \lim_{n\to\infty}S_{n_2}$$

which is only right when both the individual limits exist.


Now moving on to the problem at hand,

$$\sum_{n=1}^\infty \frac1{\sqrt{n}} -\frac1{\sqrt{n+2}}$$

$$S_n=1-\frac1{\sqrt{3}}+\frac1{\sqrt{2}}-\frac1{\sqrt{4}}+\frac{1}{\sqrt{3}}-\frac{1}{\sqrt{5}}+\cdots +\frac{1}{\sqrt{n}}-\frac{1}{\sqrt{n+2}}$$

$$S_n=1+\frac1{\sqrt{2}}-\frac{1}{\sqrt{n+2}}$$

Clearly, we have,

$$\lim_{n\to\infty} S_n=1+\frac{1}{\sqrt{2}}$$

share|improve this answer
    
I was wondering why the answer was $1$... and then I saw the edit. –  Derek 朕會功夫 Apr 4 at 5:46
    
@Derek朕會功夫 yeah typo. –  Sabyasachi Apr 4 at 5:54

Note: $$\sum_{n = 1}^\infty \left[\frac{1}{\sqrt{n}} - \frac{1}{\sqrt{n + 2}}\right] = 1 - \frac{1}{\sqrt{3}} + \frac{1}{\sqrt{2}} - \frac{1}{\sqrt{4}} + \frac{1}{\sqrt{3}} - \frac{1}{\sqrt{5}} + \frac{1}{\sqrt{4}} - \frac{1}{\sqrt{6}} + \cdots = 1 + \frac{1}{\sqrt{2}}.$$

By the way, if $\sum f(n)$ and $\sum g(n)$ diverge, it does not mean $\sum [f(n) - g(n)]$ diverges because, for example, $$\sum_{n = 1}^\infty \left[\frac{1}{\sqrt{n}} - \frac{1}{\sqrt{n + 2}}\right]$$ converges.

share|improve this answer
    
"The rule you are trying to use to disprove X is incorrect; for a counterexample, observe that X is true". I'm not sure whether that's brilliant or horrible. –  Rawling Apr 4 at 11:49
    
@Rawling If there is a counterexample, then the "theorem" is obviously not true. –  glebovg Apr 4 at 20:06
    
Well yes, but if he's trying to use it to disprove X, X isn't going to be the first counterexample that springs to mind :) –  Rawling Apr 5 at 7:03
    
@Rawling I see what you mean. –  glebovg Apr 5 at 10:22

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.